Social freedom as ideology. (September 2019) - Ng, Karen
This article explores objections made against ideal theorizing in political philosophy by two prominent contemporary critical theorists: Axel Honneth and Charles Mills. In Freedom's Right, Honneth situates his neo-Hegelian analysis of social freedom in opposition to contemporary political philosophy that has become 'decoupled from an analysis of society'. Across many works, Mills has argued that ideal theorizing in political theory is not only ineffectual, but more problematically, that it is ideological in nature and serves the interests of privileged groups. I suggest that whereas Honneth's objection to ideal theorizing hearkens back to Hegel's critique of Kant, Mills' objection that ideal theory is ideology hearkens back to Marx's critique of bourgeois political philosophy in general, and Hegel's political philosophy in particular. Against the background of these debates, I assess Honneth's theory of social freedom according to Mills' Marxian inspired ideology critique. I argue that while in some respects, Honneth's theory of social freedom is a defensible project, in other respects, Mills' critique remains instructive and allows us to see the ways in which aspects of Honneth's theory could serve ideological functions, and thus, is not entirely successful, either as a piece of critical theory or as an alternative to ideal theory.